THE INFLUENCE OF SHARIAH COMPLIANCE AND CUSTOMER PERCEPTION ON THE DECISION TO SAVE MUDHARABAH SAVINGS PRODUCTS AT BANK SYARIAH INDONESIA - Rizqiyah, Anisah; Anggraini, Tuti; Indra, Ahmad Perdana (LPPM Universitas Trunojoyo Madura, 2025)
The integrity and credibility of Islamic banks are highly dependent on compliance with Islamic principles. Non-compliance can lower public trust and affect their decision to use Islamic banking services. In addition, people's perceptions and attitudes influenced by their understanding also play an important role in the decision to save or use Islamic bank products. This research intends to analyze the influence of Shariah Compliance and Customer Perception on the decision to save mudharabah savings products for the gift party. This research uses quantitative research techniques with field research methods. The total population is 37 people, namely customers of Bank Syariah Indonesia KC Medan Ahmad Yani who have saved and used Mudharabah Savings products for Gift Parties and all pupulations are used as samples. Data collection techniques with questionnaires. The data was analyzed using the SPSS application version 27. The results of the study show that Sharia Compliance and Customer Perception together (simultaneously) have a positive and significant influence on Saving Decisions. This is evidenced by the value of F calculated 44.649 F table 3.28 and the probability of significance 0.000 0.05.